(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
The corpus of Folk Aurès songs constitutes a rich repository that enables scholars to explore the enduring anthropological and sociological frameworks undergirding the collective Aurès imaginary and traditional North African thought. By conducting a careful reading and analysis of these song texts, one gains at least a partial understanding of human nature and societal structures in the Aurès region. Moreover, these songs invoke a set of customs and festivities on the brink of extinction—if not already vanished—and illuminate residual social and cultural values that once formed the bedrock of Aurès social organization. They further serve to rationalize various local ideologies and institutions, notably marriage practices predicated on endogamy and tribal affiliations. In addition, they underscore the import of tirougza (manhood), honor, and virginity as key pillars of the region’s patriarchal system. This study employs content analysis to draw out and interpret the symbols and meanings suggested by these ritualistic functions, while simultaneously uncovering the sociological values embedded within. In doing so, it offers insight into the historical and social testimonies still discernible in the region.